Anodic oxidation for the remediation of soils polluted with perchloroethylene. Issue 1 (22nd August 2018) - Muñoz‐Morales, Martin; Sáez, Cristina; Cañizares, Pablo; Rodrigo, Manuel Andrés
Abstract: BACKGROUND: This work focuses on the removal of perchloroethylene (PCE) from soils spiked with this hazardous chlorinated hydrocarbon and oil by a combination of two technologies: soil washing and anodic oxidation with diamond electrodes. The first attains the transfer of the pollutant from the soil to a soil washing fluid (SWF), from which the organics are then efficiently removed. RESULTS: Results show that high concentrations of sodium dodecyl sulphate (SDS) are required in the SWF for an efficient extraction of the chlorinated hydrocarbon and electrolysis has to be applied not only to the clarified liquid, but also to the interphase. The surfactant used interacts strongly with soil not only during the washing, but also during the electrolysis step. This interaction seems to play a protective role against the oxidation of SDS. The initial phase of the electrolysis is rather complex and there are several processes which modify the results importantly. CONCLUSIONS: Removal of PCE by electrolysis from soil is less efficient than its removal from synthetic solutions of this chlorinated pollutant. There are two first‐order kinetic zones, which indicate an important competition for the oxidation of the different organics contained in the SWF during the electrolysis. © 2018 Society of Chemical Industry